Interregional Partnership of Russia as a Tool of Realization of National Priorities of its Economic Development - E L Andreeva; A N Golovin; A V Ratner (Vestnik RUDN. International Relations, 2015)
The analysis of interregional economic partnership existing simultaneously with the concept of traditional regionalism is proposed in the article. The cases of Trans-Pacific strategic economic partnership agreement (TPSEPA) which is created already for some decades; Transpacific agreement on strategic and economic partnership plan (2012), under which the US and the EU are going to form a Transatlantic FTA (TAFTA); initiative of Asia and Pacific countries (presented at the summit of these countries in 2012) to form a Regional comprehensive economic partnership (RCEP) are described. The case of BRICS is analyzed in details. The economic factors joining the countries - participants of the group are analyzed. The prospects of broadening of its partnership - with participation of economies of South America are highlighted. Russian external trade is touched by machinery production and accompanying services with the countries-partners mentioned. It’s shown that these economic relations can be used by Russia for solving of the tasks of substitution of import, neo-industrialization and export stimulating.